Development and preliminary validation of a new Procedural Tactical Knowledge Test for Basketball using 3vs.3 situation - Pérez-Morales, J. C.; Greco, P. J.; Ferreira-Lopes, B.; Estevão, B. J.; Ibanez, S. J. (Revista Internacional de Ciencias del Deporte, 2018)
The aim of this study was to validate an instrument for assessing procedural tactical knowledge (PTKT: Bb) of basketball players from 12 to 19 years old in 3vs.3 situations in half court (protocol A) and full court (protocol B). Evidence of content validity, reliability, and construct validity was investigated by calculating the Content Validity Coefficient (CVC), the Cohen's Kappa Coefficient and performing an exploratory factorial analysis (EFA), respectively. Content analysis was performed by 5 basketball coaches. 161 male basketball players aged between 12 and 19 years performed the protocols. The assessments of two basketball coaches were used to calculate within and between observer reliability for the PTKT: Bb. CVC values were above .80 for language clarity, theoretical relevance, and practical relevance. Cohen`s Kappa Coefficient indicated substantial within and between observer agreement for protocol A. EFA indicated two final factorial models for protocol A. Values of Kaiser-Meyer-Olkim, factor loading, and communalities were above .50 for protocol A. The percentage of explained variance was 70%. In conclusion, PTKT: Bb presented moderate psychometric properties, which suggests that procedures for validating this instrument should continue.